Key challenges across Food, Energy and Water Systems in South Asia and IMPACT - Ringler, Claudia (2018)
Presented by IFPRI Senior Research Fellow Claudia Ringler at the Foresight Workshop on "Policy Research on the Food-Energy-Water Nexus in the Eastern Gangetic Plain", Sep 7, 2016, Delhi.